Degradation of styrene from petrochemical wastewater by PSEUDOMONAS SP. [electronic resource] - 285251 Pamela Baldwin Thomas (Skudai : Universiti Teknologi Malaysia, 2007)
Project Paper (Sarjana Muda Sains (Biologi Industri)) - Universiti Teknologi Malaysia, 2007